OPTIMALISASI PEMBERDAYAAN MASYARAKAT DESA MELALUI SINERGI PROGRAM PUAP, GAPOKTAN, DAN DESA MANDIRI PANGAN (STUDI KASUS DI BEBERAPA DESA DI KABUPATEN GROBOGAN) (Faculty of Social Science, Universitas Negeri Semarang, 2016)
Community empowerment program that aims to alleviate poverty in the countryside, in principle, has many similarities. This is seen in PUAP, Gapoktan and Demapanprogram. As for the similarities among others: village-based, implemented by community groups, obtain agriculture and non-agriculture venture, establishment of micro-finance institutions at the village, and guided by extension workers and facilitators. In the implementation, the program had experienced many problems and to overcome thesecoordination is needed by synergizing PUAP, Gapoktan, and Demapanprogram. Synergies and integrations of the programs cover several aspects, namely: (1) begins with the synergy of data, the election of program recipients village; (2) internal arrangement of institutional programs; (3) strengthening of infrastructure development with the goal ofaccelerated poverty reduction; and (4) anticipation of synergy implementation of the three programs in the field. By optimizing these four aspects, it is expected that acceleration of the development of agriculture and rural economy that lead to poverty alleviation can be realized. It is based on case studies that exist in some villages in the district of Grobogan.